(untitled) - Piccoli, Gabriele (Hoboken, NJ, 2008)
Information Systems for Managers is a text for managerial/MBA students intended to actively engage them in discussions and activities around information systems and information technology. Piccoli has interwoven many real-world examples into the text that show students how IS will effect their futures in management positions. Each chapter starts off with a mini-case to get the student's attention, build excitement, and foster interactive discussions. A plethora of unique, full-length cases are also composed within the text to hold student's attention and show them how IS and IT are of great interest to them as managers.
Keywords: Management information systems,Business,Quản trị hệ thống thông tin,Kinh doanh; Data processing,Dữ kiện